Didáctica de la ética. El aporte de Mockus a la gobernabilidad en Colombia (2019)
This text takes up proposals from Antanas Mockus during his two government programs in the Mayor's Office of Bogotá, with the objective of resignifying at a historical level key moments of Mockusian governance, seen as a didactic strategy that is still viable, and applicable to the inhabitants of different cities from the country. The reflection includes a critical analysis of the government strategies developed in Bogotá, which aimed to strengthen two basic values of society: a) life and b) respect. In conclusion, the contribution of Mockus’ government program to governance in the country is indicated, which gave a place to pedagogy in Colombian politics because it generated a didactic model for the strengthening of citizen ethics, making possible new citizens, and is conceived as a great contribution to the exercise of national politics.